Road Damage Analysis, and Repair Techniques and Estimation Plan for Road Repair in Tani Bakti Village STA (00+00 – 03+00) Kutai Kartanegara Regency - Mohammad helmi irawan; Tatag Yufitra Rus; Mahfud Mahfud (Civil Engineering Dept, Balikpapan State Polytechnics, 2023)
Road damage that occurred on the road of Tani Bakti village in Kutai Kartanegara Regency, the damage factor occurred because of the need for people to use heavy vehicles to transport crops, resulting in reduced quality and life of the pavement. The purpose of this study was to determine the condition of the pavement as well as recommendations for improvement and budget plan Road Village Tani Bakti. The method used in this study is the method of highways, in determining the value of road damage conditions and calculate the pavement thickness plan. In the calculation of pavement thickness plan there are road condition data, Lhr data and Dcp data. In calculating the budget plan with AHSP 2021 balikpapan data. The results of this study indicate that the level of damage in the village of Tani Bakti has a fairly high level of damage that must be done routine maintenance of roads. Based on the results of damage analysis obtained recommendations that Overlay repair. Based on the analysis of the cost calculation, the Overlay repair cost is Rp. 14.524.436.000. Improvement on the road of Desa Tani Bakti should be focused on increasing road capacity by increasing the width of the pavement, then monitoring the damage is needed if there is damage then immediately held appropriate repairs and the existence of damage documents, Road technical data, traffic data which at times is very necessary as a basis for annual routine road handling activities.